SANKSI ADAT PADA LARANGAN PERKAWINAN EXOGAMI DI DESA PAKRAMAN TENGANAN PEGRINGSINGAN, DESA TENGANAN, KECAMATAN MANGGIS, KABUPATEN KARANGASEM, PROVINSI BALI - I Putu Sudarma; Pande Putu Toya Wisuda (Sanjiwani: Jurnal Filsafat, 2018)
Tenganan Pegrisingan Indigenous Peoples Village, Karangasem, Bali belong to Bali Aga community which is still thick with customary ban on exogamy marriage. Violations of the marriage ban are subject to customary sanctions. Customary sanctions are not only imposed on the bride, but also the parents. Customary sanction on exogamy marriage is motivated by the preservation of tradition and kinship system and balance. In the context of traditional preservation, adat sanctions are used to safeguard, maintain, and preserve endogamy as the most ideal model of marriage. In the context of the kinship system, customary sanctions are used to maintain the purity of lineages in the village. Conversely, in the context of equilibrium, adat sanctions are used for cosmic balance. The impact of adat sanction is exogamy marriage, that is, non-insurrection, does not obtain the welfare of his village, and loses the right of his village. In the context of non-divisiveness, marriage is very closed and limited because its citizens may only engage in endogamous marriage among their own adat folk. In the context of not obtaining the welfare of the village means a violation of endogamy, practically all bridegroom rights including the right to obtain the welfare of his village is lost. In the context of lost rights, all rights are revoked so that the bride has absolutely no rights in his village.